Light-driven soft robot with compound motion patterns based on gas–liquid phase transition chamber - Zheqi Zhou; Kejian Chen; Yang Shen; Yifan Zhu; Qian Wang; Xiaofen Zeng; Yuke Qin; Songlin Zhuang (Scientific Reports)
Abstract Light is increasingly being used to drive soft robots and soft actuators. In this paper, a light-driven soft robot with compound motion patterns based on gas-liquid phase transition chamber is proposed, which inspired by the frog and the larvae of gall midges. When a light source with a power density of about 1.25 W/cm2 is illuminated on the upper surface of the auxiliary pneumatic chamber, the previously non-existent main pneumatic chamber can be expanded quickly within less than 3 s, and generate enormous thrust. This allows the soft robot (length: 3 cm; width: 0.7 cm; weight: 0.36 g) to quickly release from the magnet attractive field and perform a jump with a height of 50.8 cm in less than 1 s, approximately 16 times the body length of the entire soft robot. The proposed soft robot can also be combined with a photothermal bending film to achieve directional crawling. At the same time, by fixing the foot of the soft robot on the base and using light irradiate it, an object weighing about 5 times the overall weight can be ejected to a horizontal distance of 16.9 cm. This untethered pneumatic soft robot has broad prospects in soft jumping robots and wireless actuators, and the proposed pneumatic triggered chamber can also be further applied to other application fields.